2017
DOI: 10.4067/s0718-95162017000400001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and biomass of a mine soil with different organic and inorganic treatments and native plants

Abstract: Heavy metals far in excess of trace amounts that are required for healthy plant growth, cause harmful effects on soil microorganisms; however, studies concerning the characterization of microbial communities in mine soils are scarce. The present study is the first attempt to characterize, by means of the analysis of phospholipid fatty acid (PLFA) patterns, soil microbial community composition from a contaminated mine soil (Pb, As) subjected to different remediation technologies. A pot experiment was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…The application of different amounts of rice husk and oil palm shell ash and a low amount of coal fly ash increased C mineralization and MBC, while the application of a high amount of coal fly ash reduced C mineralization and MBC. The results of this study are consistent with a study by Basanta et al (2017) that reported changes in both microbial activity and microbial biomass after the application of remediation treatments. Ash application to soils indirectly influences soil C mineralization and MBC through changes in the activity of soil microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…The application of different amounts of rice husk and oil palm shell ash and a low amount of coal fly ash increased C mineralization and MBC, while the application of a high amount of coal fly ash reduced C mineralization and MBC. The results of this study are consistent with a study by Basanta et al (2017) that reported changes in both microbial activity and microbial biomass after the application of remediation treatments. Ash application to soils indirectly influences soil C mineralization and MBC through changes in the activity of soil microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…These fungal isolates exhibited the great ability to solubilize P, increase the growth of eggplant, and produce siderophores and indole acetic acid [6]. In addition, the use of organic residues as amendments exerts a great influence on soil microbial communities [45][46][47][48], which not only increases the soil organic matter level and long-term soil fertility, but also improves the soil health and productivity.…”
Section: Effects Of Different Organic/chemical Amendments In Rhizosph...mentioning
confidence: 99%
“…Studies to evaluate the use of SAPs on the microbiological properties of post-industrial soils are rare and limited to mine soils contaminated with toxic metals [182,187]. These studies reported a positive effect of SAP application on soil microbiological properties [168,169,[187][188][189], resulting from increased pH and significantly reduced concentrations of toxic metals in the soil solution.…”
Section: The Influence Of Superabsorbents On the Microbiological Acti...mentioning
confidence: 99%